ADVANCEMENT OF TiO2-BASED PHOTOCATALYST FOR PHOTODEGRADATION OF ORGANIC POLLUTANTS IN WASTEWATER - Noor, Nurul Adilah Mohd; Sidik, Siti Munirah; Rosmi, Mohamad Saufi; Hitam, Che Ku Nor Liana Che Ku; Jaafar, Nur Farhana (CENTRAL ASIA AND THE CAUCASUS, 2022)
Photocatalytic degradation has gained attention as an environmental friendly technology as it offers mild reaction conditions for wastewater treatment. The present review mainly describes the strategies to improve the photodegradation of organic pollutants through modification of TiO2-based photocatalyst since TiO2 has several disadvantages, like wide band gap (Eg) (3.2 eV) and quick recombination of photogenerated charges that inhibit its full potential towards photocatalysis. Therefore, much effort to obtain excellent photocatalytic performance that includes using mesoporous materials and the addition of metal doping into the TiO2 are highlighted to propose a mechanistic study of promising photocatalytic method. Incorporating mesoporous materials within the TiO2 enhance the interaction of organic pollutant and photocatalyst as it produces large surface areas that improve the photocatalytic activity. Doping with metal will suppress the recombination between electron/hole pairs produced on photon absorption as it acts as electron sinks that may improve the photocatalytic performance by the quantum yield of superoxide radicals.